PENINGKATAN KEMAMPUAN MENULIS BERITA DENGAN MENGGUNAKAN AUDIOVISUAL PEMBELAJARAN ONLINE KELAS VIII SMP NEGERI 35 MAKASSAR - A. Vivit Angreani; St. Naisa Hehanussa (KLASIKAL : JOURNAL OF EDUCATION, LANGUAGE TEACHING AND SCIENCE, 2022)
The aim of this research to get the data and information about using audiovisual to improving wiriting- news skill online teaching in 8th grade on SMP Negeri 35 Makassar. With population 33 students. The technic of data analysis is using test and obseration. The result of data analysis shows improving writing- news skill is signiticant with using online teaching. After did the 2nd cycle, this was proven from 1st cycle the average was 80% and 2nd are 85,32%. In conclusion, the improving writing- news using audiovisual online in 8th grade on SMP Negeri 35 Makassar.